Pyk2 suppresses contextual fear memory in an autophosphorylation-independent manner. (16th September 2021) - Zheng, Jin; Suo, Lun; Zhou, Yuxiao; Jia, Liling; Li, Jingwei; Kuang, Yanping; Cui, Donghong; Zhang, Xuehong; Wu, Qiang
Abstract: Clustered protocadherins (Pcdhs) are a large family of cadherin-like cell adhesion proteins that are central for neurite self-avoidance and neuronal connectivity in the brain. Their downstream nonreceptor tyrosine kinase Pyk2 (proline-rich tyrosine kinase 2, also known as Ptk2b, Cakb, Raftk, Fak2, and Cadtk) is predominantly expressed in the hippocampus. We constructed Pyk2- null mouse lines and found that these mutant mice showed enhancement in contextual fear memory, without significant change in auditory-cued and spatial-referenced learning and memory. In addition, by preparing Y402F mutant mice, we observed that Pyk2 suppressed contextual fear memory in an autophosphorylation-independent manner. Moreover, using high-throughput RNA sequencing, we found that immediate early genes, such as Npas4, c Fos, Zif268/Egr1, Arc, and Nr4a1, were enhanced in Pyk2- null mice. We further showed that Pyk2 disruption affected pyramidal neuronal complexity and spine dynamics. Thus, we demonstrated that Pyk2 is a novel fear memory suppressor molecule and Pyk2- null mice provide a model for understanding fear-related disorders. These findings have interesting implications regarding dysregulation of the Pcdh‒Pyk2 axis in neuropsychiatric disorders.